KINDNESS IN LEWIS'S THE CHRONICLES OF NARNIA : THE LION, THE WITCH AND THE WARDROBE - Injili Aruperes; Olga A. Rorintulus; Fivy Andries (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
In this study, the writer intens to revealed that there is kindness in the story of “The Chronicles of Narnia: The Lion, The Witch and The Wardrobe”. This study is a qualitative research. The approach is used namely objective research. This study show that kindess is depected through the character of “The Lion”. In this case, the findings in this research was found from the writer about kindness in the character based on the story. The character of the Lion being the center of the story and relates to love, wisdom, sacrifice, being helpful and respected but it also can found in another character that’s have a relation with the character of the Lion. The love can be found on the character on the pevensie siblings: Susan, Peter, Lucy, Edmun. The wisdom can be found on the character of Susan. The sacrifice can be found on the character of Beaver and Mr.Tumnus and he also have the aspect of being helpful. From the kindness in the character of the Lion, concludes that the story of “The Chronicles of Narnia: The Lion, The Witch and The Wardrobe”, contains good values ​​that can be learned and applied in life and there’s any relation between the story of “The Chronicles of Narnia: The Lion, The Witch and The Wardrobe” with the value of kindness especially on the character of “The Lion”.